TEACHER STRATEGIES IN STIMULATING THE CREATIVITY OF 5-6 YEAR-OLD CHILDREN THROUGH RECYCLING ACTIVITIES AT AL-HIKMAH PAUD, TANARA DISTRICT - Haorah; Mahsiani Mina Laili; Yoga Mahendra; Yolanda Pahrul; Nuryati (Cakrawala Pedagogik, 2025)
This study aims to describe the teacher’s strategies in stimulating the creativity of children aged 5-6 years through recycling activities at PA UD Al-Hikmah, Tanara District. Creativity in early childhood is an essential aspect that should be developed from an early age, encompassing the ability to take initiative, process materials, and produce original works. This research employed a qualitative approach with a descriptive method. The subjects consisted of teachers and Group B children. Data were collected through observation, interviews, and documentation. The data analysis involved data reduction, data display, and conclusion drawing. The results showed that teachers implemented learning strategies based on play, experimentation, and projects. Through these activities, children were encouraged to explore various recyclable materials such as cardboard, plastic bottles, and used paper. These strategies effectively enhanced children’s creativity indicators, namely the emergence of initiative, skills in processing materials into functional products, and the ability to create unique and aesthetic works. Supporting factors included the availability of recyclable materials, active teacher involvement, and the supportive school environment. This study recommends the continuous use of recycling activities as an effective medium to stimulate creativity in early childhood